Engineering in dependability of computer systems and networks : proceedings of the fourteenth International Conference on Dependability of Computer Systems DepCoS-RELCOMEX, July 1–5, 2019, Brunów, Poland /: proceedings of the fourteenth International Conference on Dependability of Computer Systems DepCoS-RELCOMEX, July 1–5, 2019, Brunów, Poland. ([2020]) - Unknown
No abstract available